Sustainable use of the natural resources of the Tentzo ecological reserve in the municipality of San Juan Atzompa, Puebla - Ayon , Donaldo Barrales; Torres, Fidel García; Olmos , Claudia Domínguez; Tovar , Edgardo Roldán y; Regules, Behetzaida Martínez; Ramos, Rosalina Lezama (Seven Editora, 2023)
The municipality of San Juan Atzompa is located within the area of the Sierra del Tentzo state reserve, which was declared a protected natural area, with 57,815 hectares in 13 municipalities of the state of Puebla, said the reserve is home to a large number of animal species. and vegetables, endemic and of economic importance for its inhabitants; hence the importance of using natural resources sustainably through the proposal of an ecotourism service that is provided by the inhabitants of the municipality of San Juan Atzompa and serves as a support in the preservation of biological, social, cultural and economic value. from the area. DOI: https://doi.org/10.56238/devopinterscie-087